1986
DOI: 10.1042/cs0710245
|View full text |Cite
|
Sign up to set email alerts
|

Kidney protection by pretreatment with free radical scavengers and allopurinol: Renal function at recirculation after warm ischaemia in rabbits

Abstract: Renal function and morphology were studied before and after 60 min of renal ischaemia and contralateral nephrectomy in five groups of rabbits. The animals were pretreated with superoxide dismutase, catalase, allopurinol or mannitol. One group was not pretreated and served as a control. A moderate transient increase in serum creatinine concentration was observed in the control rabbits, while a significantly less pronounced increase was noted after pretreatment with superoxide dismutase, catalase and mannitol. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
1
17
1
Order By: Relevance
“…[40] showed that SOD was able to inhibit the postischemic increase in vascular permeabili ty. Hansson et al [41] showed a protective effect in the kidney after ischemia by radical scavengers, such as SOD and mannitol. In the hamster cheek pouch.…”
Section: Discussionmentioning
confidence: 99%
“…[40] showed that SOD was able to inhibit the postischemic increase in vascular permeabili ty. Hansson et al [41] showed a protective effect in the kidney after ischemia by radical scavengers, such as SOD and mannitol. In the hamster cheek pouch.…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs have been studied in the protection of the kidney from I/R injury (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The anti-anginal medication trimetazidine (TMZ) has been shown to protect the myocardium cells through inhibition of fatty acid oxidation and reciprocal activation of pyruvate oxidation, resulting in less production and accumulation of lactate and hydrogen cation, H+, during ischaemia (14).…”
mentioning
confidence: 99%
“…Several reports show that antioxidants protect while others show no protection [51][52][53][54]. To clarify this problem and better understand how anoxia affects the sensitivity to oxidant injury, we have performed in vitro studies in which isolated hepatocytes are exposed to both controlled periods of anoxia and controlled oxidant loads.…”
Section: Ischemia Reoxygenation Injury and The Selective Vulnerabilimentioning
confidence: 99%